49.0k views
13 votes
Whats is a 3 step problem that can represent the expression 3x + (-5) = 19 I dont want the answer to x i just want a different version of the problem that takes 3 steps to do

2 Answers

7 votes

Answer:

Explanation:

The expression 3x + (-5) = 19 is actually an equation, not an expression. To solve this, we calculate the value of x that makes this equation true.

1) Start by adding 5 to both sides: 3x + (-5) + 5 = 19 + 5. We get 3x = 24

2) Divide both sides of this result by 3 to isolate x: x = 8

3) Check this result. If we substitute 8 for x in the original equation, is the resulting equation true? Yes: 3(8) + (-5) = 19

User Castaldi
by
5.0k points
8 votes

3x + -5 = 19 is a two-step equation where you would have to add and divide to solve. One more step could be combining like terms:

3x + -5 - 19 =0

OR

2x + -5 + x = 19

OR an additional third step could be square root.

(3x + -5)^2 = 19^2

OR an additional third step could be square it.

sqrt(3x + -5) = sqrt(19)

User Qloq
by
5.5k points